2020
DOI: 10.1093/pubmed/fdaa095
|View full text |Cite
|
Sign up to set email alerts
|

Greater risk of severe COVID-19 in Black, Asian and Minority Ethnic populations is not explained by cardiometabolic, socioeconomic or behavioural factors, or by 25(OH)-vitamin D status: study of 1326 cases from the UK Biobank

Abstract: Background We examined whether the greater severity of coronavirus disease 2019 (COVID-19) amongst men and Black, Asian and Minority Ethnic (BAME) individuals is explained by cardiometabolic, socio-economic or behavioural factors. Methods We studied 4510 UK Biobank participants tested for COVID-19 (positive, n = 1326). Multivariate logistic regression models including age, sex and ethnicity were used to test whether addition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
304
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(342 citation statements)
references
References 19 publications
29
304
0
9
Order By: Relevance
“…Our analyses showed that the racial composition of zip codes was robustly associated with the incidence of COVID-19 during a state-mandated lockdown. This support other studies both within and outside the USA which have demonstrated that Blacks and ethnic minorities bear a higher brunt of COVID-19, not fully explained by traditional risk factors [ 31 ]. As the COVID-19 pandemic continues to unfold across communities across the USA, it is important to identify vulnerable populations, and institute policies that will reduce the adverse effects of COVID-19 in these populations.…”
Section: Discussionsupporting
confidence: 90%
“…Our analyses showed that the racial composition of zip codes was robustly associated with the incidence of COVID-19 during a state-mandated lockdown. This support other studies both within and outside the USA which have demonstrated that Blacks and ethnic minorities bear a higher brunt of COVID-19, not fully explained by traditional risk factors [ 31 ]. As the COVID-19 pandemic continues to unfold across communities across the USA, it is important to identify vulnerable populations, and institute policies that will reduce the adverse effects of COVID-19 in these populations.…”
Section: Discussionsupporting
confidence: 90%
“…The recommendations are silent on the critical issues of employment security, adequate safety nets, and the causes of occupational segregation. Similarly, nothing is said about a longstanding need to reduce household overcrowding, a key candidate for covid-19 transmission 14. Social housing restrictions on local authorities impair adequate housing provision for larger and multigenerational households.…”
mentioning
confidence: 99%
“…Women are more likely to avoid crowds and use of public transport than men (9,10); older age is often associated to engagement with SD behaviours (9)(10)(11), though other studies have found no conclusive evidence (12,13). Black, Asian and Minority Ethnic (BAME) populations in the UK have been found to be at greater risk of dying from COVID-19 compared to the white population (14), and evidence suggest this is multi-factorial (material deprivation, increased exposure to risk and structural racism amongst others (15), yet ndings from previous pandemics and COVID-19 suggest that this is not due to poorer adherence to SD measures (16,17). Higher socio-economic status and higher educational attainment are often related to engagement in SD behaviours (10)(11)(12)18), although both low income and having no quali cations have also been associated with greater adherence to SD behaviours in a UK study (16).…”
Section: And the Independent Sagementioning
confidence: 99%